Comments on public health and fetal and neonatal maternal care in the SARS-CoV-2 virus pandemic - Cueva-Buendía, Luis Alberto (2020)
For the time that the pandemic has in Peru since it became official on March 6, and due to the reality that we are living, there must be pregnant women who have been exposed from the first trimesters of gestation to COVID-19, therefore we should manage better childbirth and the puerperium, to guarantee a good recovery for the positively diagnosed mother and the newborn. There is also an urgent need to reach a consensus on perinatal and neonatal management in Peru.